Sociodemographic, Psychosocial and Health-Related Factors as Predictors of Physical Activity Levels Among Adolescents - Dan, Siew Peng (2007)
A cross-sectional study was conducted to determine factors associated with physical activity levels of four hundred, 13 year-old adolescents in Kuantan, Pahang. Physical Activity Questionnaire for Older Children (PAQ-C) was used to assess physical activity levels among the participants. Data on sociodemographic, psychosocial and health related factors were collected using self-administered questionnaire. The respondents comprised of 41.8% males and 58.2% females encompassed 56.2% Malays, 42.0% Chinese, and 1.8% Indians. Results indicated that more than one third of the respondents were in the low physical activity level category, most (61.5%) were in the moderate category and only 3.0% of the respondents were in the high physical activity level category. Males were more physically active than females (2=23.667, p=0.0001). Female adolescents (45.1%) were twice as likely as male respondents (22.1%) to fall in the low physical activity level category. The association between physical activity level and ethnicity was not significant. However, there was a significant interaction effect of sex and ethnicity in mean physical activity score (F=8.343, p=0.004). Malay males have a higher mean physical activity score compared to Chinese males while Chinese females have a higher mean physical activity score than Malay females. There were no significant association between sociodemographic factors and physical activity except father’s total years of schooling (r=0.105, p<0.05). Health-related factors studied (body mass index, smoking and eating behaviors) were found not correlated with physical activity. For psychosocial factors, physical activity was found positively and moderately correlated with physical activity self-efficacy (r=0.496, p=0.0001) and peer influence (r=0.468, p=0.0001). A low and positive relationship was found between physical activity with family influence (r=0.298, p=0.0001) and beliefs for physical activity outcome (r=0.207, p=0.0001) while a negative and weak relationship was found between physical activity and depression (r=- 0.116, p=0.021). Moreover, respondents who have better perception of their current health status were more physically active (2=21.062, p=0.0001). Physical activity was found not correlated with perception of weight status and body parts satisfaction. However, a negative relationship was found between physical activity and body size discrepancy (r=-0.143, p<0.01). Multivariate analyses for the prediction of physical activity showed that physical activity self-efficacy, sex and peer influence were found to be significant in explaining physical activity among adolescents. This study suggests that physical activity intervention should include physical activity self-efficacy and social influence components in intervention designed to promote regular physical activity in adolescence.